Determinan Perilaku Merokok pada Remaja Sekolah di Indonesia - Titik Harsanti; Febri Wicaksono (Jurnal Aplikasi Statistika & Komputasi Statistik, 2017)
Smoking is a global public health concern and it imposes a heavy economic burden. However, the trend of smoking in Indonesia seems to be increasing and the magnitude of the problem affects not only adults but also adolescents. This paper identifies cigarette smoking determinants among school adolescents in Indonesia, using a multivariate binary logistic model. The analysis uses 5,986 samples of students from the 2014 Indonesia Global Youth Tobacco Survey (GYTS). The results show that 25% of the students have ever smoked and 15% of students are currently smoking. The students’ odds of smoking are higher for boys compared to girls. Higher risk of smoking is observed among the students who have closed-peer smoking compared to students who don’t have closed-peer smoking. Students whose one or both parents are smoking are more likely to smoke compared to whose parents are not smoking. Students who have seen their teacher smoking or have seen people smoking in their house and public places are more likely to smoke compared to who haven’t ever seen their teacher smoking or haven’t ever seen people smoking in their house and public places. These findings suggest that enforcement of legislations to decrease accessibility of cigarettes are necessary to curb the cigarette use among students. Beside that the interventions and education campaigns that target secondary school students are also needed.